Effectiveness of Red Dragon Fruit Juice in Reducing Blood Glucose Levels among Elderly Patients with Type II Diabetes Mellitus - Febriyanti Febriyanti; Meria Kontesa; Em Yunir; Elsyie Yuniarti; Mira Andika; Mitayani Mitayani; Yani Maidelwita; Eka Putri Primasari (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Type II Diabetes Mellitus (T2DM) is a major chronic health problem among the elderly, characterized by persistent hyperglycemia and increased risk of complications. Alongside pharmacological therapy, safe and affordable non-pharmacological interventions are needed to support glycemic control. Red dragon fruit (Hylocereus polyrhizus) contains dietary fiber and bioactive compounds with potential hypoglycemic effects. This study aims evaluate the effect of red dragon fruit juice on fasting blood glucose levels in elderly patients with Type II Diabetes Mellitus (T2DM). A quasi-experimental pretest–posttest control group design was employed. Fifty elderly patients aged 60-75 years with Type II Diabetes Mellitus were recruited through purposive sampling and assigned to an intervention group (n = 25) or a control group (n = 25). The intervention group received red dragon fruit juice (200–250 mL/day) for 14 days, while the control group received standard care. Fasting blood glucose levels were measured before and after the intervention and analyzed using paired sample t-tests. The intervention group demonstrated a significant reduction in mean fasting blood glucose from 139.20 mg/dL to 121.40 mg/dL, with a mean difference of 17.80 mg/dL (p = 0.001). In contrast, the control group exhibited only a slight decrease from 138.60 mg/dL to 136.80 mg/dL, with a mean difference of 1.80 mg/dL, which was not statistically significant (p = 0.075). These findings indicate that red dragon fruit juice significantly reduces fasting blood glucose levels in elderly patients with Type II Diabetes Mellitus (T2DM). This intervention may be considered a safe and practical complementary nutritional therapy to support diabetes management in the elderly.Keywords: Type II Diabetes Mellitus, Red Dragon Fruit Juice, Fasting Blood Glucose, Elderly, Complementary Nutrition.